Hand function in rheumatic diseases: patient and physician evaluations. (8th October 2014) - López López, Carlos Omar; Alvarez‐Hernández, Everardo; Medrano Ramirez, Gabriel; Montes Castillo, Ma Luz; Hernández‐Díaz, Cristina; Ventura Rios, Lucio; Arreguin Lopez, Roberto; Vázquez‐Mellado, Janitzia
Abstract Aim Rheumatic diseases have repercussions in hand function. The m‐SACRAH (modified Score for the Assessment and quantification of Chronic Rheumatoid Affections of the Hands) questionnaire evaluates hand function according to the patient's opinion. Our aim was to look for the clinical and para‐clinical variables that correlate with m‐SACRAH in rheumatic diseases. Methods Consecutive patients with diagnoses of rheumatoid arthritis (RA), osteoarthritis (OA), gout, and systemic sclerosis (SS) with hand involvement and who agreed to participate, answered the m‐SACRAH and Health Assessment Questionnaire Disability Index (HAQ‐DI) and underwent blinded and independent rheumatologist and physiatrist evaluations. Nerve conduction studies (NCS) and hand ultrasonography (USG) were performed. Statistical analysis: Spearman's correlation and the Mann–Whitney U‐test. Results Forty patients were included. There were 72% women and mean age of 49.25 ± 14.2 years. According to m‐SACRAH patients were dived into two groups (mild vs. moderate‐severe), only the number limited to motion joints were different among them (median 2 vs. 8 P = 0.036). Patients' perspective variables had a good correlation (HAQ‐DI/mSACRAH: r = 0.43, P < 0.05), but only correlated with limited motion joints (r = 0.41, P < 0.05 for m‐SACRAH and r = 0.31, P < 0.05 for HAQ‐DI). Physician′s evaluations had a good correlation. Visual analog scale of hand function with physiatrist evaluations: passive range of motion (r = −0.49, P = 0.001), sum of affected pinches (r = 0.66, P = 0.001), limited to motion joints (r = 0.34, P < 0.05) and palm‐finger distance (r = 0.50, P = 0.05). Regarding para‐clinical evaluations, only tenosynovitis by ultrasonography correlated with HAQ‐Di (r = 0.357, P < 0.05). Conclusions Patients' perspectives correlated with the number of limited motion joints but with none of the other physicians' and para‐clinical evaluations. The patients' opinion about their function should play a major role in their management.